Comparison of a Distal Tibial Allograft and Scapular Spinal Autograft for Posterior Shoulder Instability With Glenoid Bone Loss. Issue 7 (18th July 2018) - Nacca, Christopher; Gil, Joseph A.; DeFroda, Steven F.; Badida, Rohit; Owens, Brett D.
Background: Posterior glenoid bone deficiency can occur with recurrent glenohumeral instability. Glenoid reconstruction with a distal tibial allograft (DTA) has been reported to successfully restore contact pressures that occur during posterior glenohumeral translation. However, there are concerns regarding the risk of allograft resorption, availability, and costs. Extracapsular reconstruction using a scapular spinal autograft (SSA) has been reported as an alternative technique secondary to its anatomic location relative to the posterior shoulder and preferable autograft properties. There are no known prior biomechanical studies evaluating the scapular spine as an effective extracapsular graft choice. Purpose: To compare the efficacy of a DTA and SSA in restoring the stability of a glenoid with a large posterior bone defect compared with the intact native glenoid. Study Design: Controlled laboratory study. Methods: Ten cadaveric shoulders were tested. With the use of a custom KUKA robot, a 50-N compressive force was applied to the glenohumeral joint. The peak force required to translate the humeral head beyond the glenoid lip posteriorly as well as the lateral displacement that occurred during posterior translation were measured. Testing was performed in 5 conditions: (1) intact glenoid and labrum, (2) simulated reverse Bankart lesion, (3) 12-mm posterior glenoid defect, (4) glenoid defect reconstructed with a fresh DTA, and (5) glenoid defect reconstructed with an SSA. Results: The mean glenoid width was 30 mm. The mean peak force and lateral displacement decreased significantly with a glenoid defect (0.99 ± 2.3 N and 0.06 ± 0.09 mm, respectively; P < .0001) compared with the intact glenoid (23.00 ± 9.7 N and 1.83 ± 0.70 mm, respectively; P = .0001). There was no significant difference between the peak force after reconstruction of the defect with a DTA (23.00 ± 7.4 N) and SSA (23.00 ± 7.7 N) when compared with the intact glenoid ( P = .9999). There were no significant differences in the peak force between the 2 grafts ( P = .9999). Additionally, both the DTA (1.04 ± 1.09 mm) and the SSA (1.02 ± 1.17 mm) demonstrated no differences in lateral displacement when compared with the intact glenoid ( P = .2336 and .2043, respectively). There was no difference in lateral displacement that occurred between the DTA and SSA ( P = .9999). Conclusion: Reconstruction of a large posterior glenoid defect with either a DTA or an SSA can effectively restore glenohumeral stability. Clinical Relevance: This study supports the use of a DTA or SSA in posterior glenoid defect reconstruction. Clinical studies are needed to determine the long-term effects of utilizing such grafts.